Improvement of the Logistic Processes using the Reverse Logistics Concept - Zbigniew Lukasik; Aldona Kuśmińska-Fijalkowska; Sylwia Olszańska (Communications - Scientific letters of the University of Zilina, 2021)
Reverse logistics differs significantly from such fields as management of waste, of which the goal is, above all, efficient and effective collection and processing of waste. Therefore, it can be said that reverse logistics refers to such streams of flows in which it is possible to recover the value from discontinued products and situation, in which solution is contribution to a new supply chain. Therefore, in this aspect, the fundamental pillar is transport, in which the crucial element is management of transport process, above all, planning of changes improving this process to better control the degree of their execution.In this article, the authors examined transport process in a real object in the context of improvement. As a result, practical aspects of planning and control of organization of transport were presented.